1990
DOI: 10.1051/rnd:19900409
|View full text |Cite
|
Sign up to set email alerts
|

Effets des alginates et des carraghénates de sodium associés aux protéines de soja sur le coefficient d'efficacité protéique (CEP)

Abstract: Daily protein intake and weight gain of casein-fed rats were not significantly different (P < 0.05) from those of rats fed soybean meal with alginate, whatever the dose received. Rats fed 3% carrageenan in soybean meal had significantly higher feed intake than that of rats fed casein. At the levels studied, alginate had no effect on the Protein Efficiency Ratio (PER), but carrageenan did. The addition of increased quantities of carrageenan to soybean meal followed by heating the mixture led to a progressive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
(6 reference statements)
0
2
0
3
Order By: Relevance
“…The ability of proteins and polysaccharides to induce the formation of complexes could have consequences on the physiological fate of proteins. Low protein hydrolysis, decrease of hydrolyzed protein absorption, and decrease of animal growth are generally observed with addition of soluble polysaccharides to foods at low or high levels (Jenkins et al, 1978, Shah et al, 1982Low and Rainbird, 1984;Schneeman and Gallaher, 1985;Mouécoucou et al, 1990Mouécoucou et al, , 1995Astwood and Morris, 1992;Larsen et al, 1994;Eggum, 1995;Ellis et al, 1995;Hsu et al, 1996;Grala et al, 1999;El Kossori et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of proteins and polysaccharides to induce the formation of complexes could have consequences on the physiological fate of proteins. Low protein hydrolysis, decrease of hydrolyzed protein absorption, and decrease of animal growth are generally observed with addition of soluble polysaccharides to foods at low or high levels (Jenkins et al, 1978, Shah et al, 1982Low and Rainbird, 1984;Schneeman and Gallaher, 1985;Mouécoucou et al, 1990Mouécoucou et al, , 1995Astwood and Morris, 1992;Larsen et al, 1994;Eggum, 1995;Ellis et al, 1995;Hsu et al, 1996;Grala et al, 1999;El Kossori et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…La première période avait pour but l'étude de l'influence des interactions entre les protéines de soja et les épaississants sur le coefficient d'efficacité protéique et les résultats ont été publiés (Mouecoucou et al, 1990). Lors de la deuxième période expérimentale, nous avons observé les effets de la renutrition sur l'évolution pondérale des rats des différents lots.…”
Section: éTude Expérimentaleunclassified
“…Selon les périodes, la quantité de farine nécessaire pour avoir 10 ou 20% de protéines a été pesée, le contenu en lipides de chaque régime a été ajusté à 9 ou 5% avec de l'huile d'arachide (Lesieur) en tenant compte du pourcentage de lipides contenu dans les farines. La composition physico-chimique de cette farine et le mode de préparation des régimes ont été décrits précédemment (Mouecoucou et al, 1990). Au cours de la deuxième période, tous les rats ont reçu le même régime standard (UAR, Villemoisson/Orge, France).…”
Section: Nature Des Régimesunclassified
See 1 more Smart Citation
“…In previous studies, the authors have observed that the ingestion of heated mixtures of soya bean meal and J MouPcoucou, C Villuun~e, H-M BUM, J -P Nicdus, L Mkjean in protein efficiency ratio (PER) but also to growth retardation in rats which cannot be restored to the level obtained by a standard diet (Mouecoucou et al 1990(Mouecoucou et al , 1991. As sulphur amino acids are limiting in soya bean proteins, it is tempting to think that carrageenan reduces protein availability and consequently methionine and induces protein malnutrition.…”
Section: Introductionmentioning
confidence: 99%